Place and Large Landscape Conservation along the Susquehanna River. Issue 2 (1st February 2018) - Green, Brandn; Jones, Kristal
ABSTRACT: Place theory can be used in natural resource sociology as a heuristic for identifying and incorporating differences in human and natural systems into large landscape conservation efforts. This paper draws on theories of place and applies mixed methods to understand the potential opportunities and challenges for a large landscape conservation initiative along the Susquehanna River. The research utilized key informant interviews of 62 conservation officials to develop a grounded theory of regions within the river corridor. These regions were used as the sampling frame for a telephone survey of approximately 1, 000 residents. Analysis of attitudes about conservation actors, priorities, and place perceptions were layered with data acquired in key informant interviews to produce an understanding of social, physical, and symbolic aspects of the Susquehanna River landscape as a place. Identifying similarities and differences can aid in the integration of human perceptions and attitudes within large landscape conservation efforts.